Comparative Analysis of Lignins of Various Plant Forms by 31P NMR Spectroscopy - Popova, Yu. A.; Shestakov, S. L.; Kozhevnikov, A. Yu; Kosyakov, D. S.; Sypalov, S. A. (Russian journal of bioorganic chemistry, 2020)
— Lignin is one of the most abundant biopolymers. Information about the functional composition and structure of various lignins may be useful in the study of biosynthesis processes in plants. The subject of the article is the determination of 31 P NMR spectroscopy possibilities to identify lignins obtained from various plant forms. To obtain spectra on 31 P nuclei, a modification of the studied samples was applied by phosphitylating their OH-groups with a special reagent. We obtained qualitative and quantitative analysis of samples of softwood and hardwood lignins and herbaceous plants. According to the NMR spectra we noted the differences in composition and structure of the studied lignins. We confirmed that the structure of lignins of softwood and hardwood wood mainly contain guaiacilpropane and syringylpropane structural units, respectively. We found that lignins of herbaceous plants contain all types of OH-groups characteristic for lignins, including p -hydroxyphenyl groups. It was observed that samples of herbaceous plants lignins contain fragments of flavonoid structures in most cases. The 31 P NMR spectrum of quercetin, as the flavonoids representative, was registered and also modeled using the ACDLabs software package to confirm the presence of flavone structures in the macromolecules of the herbaceous lignins.